Determinant Factors of Stunting Among Toddlers in Riverbank Areas: A Case-Control Study - Fathurrahman Fathurrahman; Magdalena Magdalena; Siti Mas’odah; Hammad Hammad; Rutmauli Hutagaol (JURNAL INFO KESEHATAN, 2025)
Stunting remains a critical issue of chronic malnutrition, especially in regions with abundant food resources but poor sanitation and nutrition education. This study aims to analyze the determinants of stunting among toddlers in the riverbank areas of Aluh-Aluh District, Banjar Regency, South Kalimantan. A case-control design was used, involving 142 children (72 cases and 70 controls) selected randomly from two villages. Variables examined include the dietary patterns of children and pregnant women, maternal nutritional status (chronic energy deficiency), exclusive breastfeeding, a history of infections, drinking water sanitation, and household food expenditure. Multivariate logistic regression revealed six significant determinants of stunting: poor maternal diet (OR=5.404), maternal undernutrition (OR=11.546), lack of exclusive breastfeeding (OR=3.198), inadequate toddler diet (OR=2.600), unboiled tap water consumption (OR=2.767), and high household food expenditure (OR=6.111). Despite being a food-rich region, the high stunting prevalence reflects structural issues in maternal education, childcare practices, and sanitation access. These findings highlight the need for contextual, integrated, and community-based interventions targeting the First 1000 Days of Life. Stunting prevention efforts should prioritize maternal nutrition education, exclusive breastfeeding promotion, improved sanitation, and the utilization of local resources and village funding.